PALAEOLITHIC LOESS-SITE YEZUPIL ON DNISTER (UKRAINE) - STRATIGRAPHY, ENVIRONMENT AND CULTURES - Boguckyj A.; Cyrek K.; Konecka-Betley K.; Łanczont M.; Madeyska T.; Nawrocki J.; Sytnyk O. (My University, 2001)
Yezupil is the first Middle Palaeolithic site discovered in upper part of the Dnister River valley. It is situated in a set of sediments composed of loess and fossil soils lying on alluvia. The results of geological and palaeopedological investigations are presented. They contain lithological and geochemical analyses (main components and trace elements), as well as micromorphological study. Palaeo- and petromagnetic record is presented too. Horohiv pedocomplex developed from the older, Wartanian loess. It is composed of luvisol originated during the Eemian interglacial and chernozem soil - during the Early Vistulian interstadials. An subarctic brown Dubno soil dated to the Interplenivistulian (Middle Vistulian interstadials) separates two parts of the younger loess. Older assemblage of Middle Palaeolithic - Mousterian culture with Levalloisian technique was found in the E horizon of the luvisol and therefore it could be dated to the Eemian interglacial. Younger Middle Palaeolithic - Micoquian-type materials were situated in partially redeposited by solifluction, Early Vistulian chernozem. Scanty and uncharacteristic Upper Palaeolithic assemblage was found in interstadial Dubno palaeosol.